TECHNIQUE OF solving MULTIFACTORIAL TARGET ALLOCATION IN AUTOMATED CONTROL SYSTEMS - S. V. Kruglikov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The technique of multivariate target distribution allowing to realize rational and effective utilization of diverse and heterogeneous objects of control in an aggressive environment is considered.